2020
DOI: 10.1177/1971400920959070
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal brain magnetic resonance imaging of children with perinatal Chikungunya encephalitis

Abstract: Chikungunya virus can be transmitted perinatally leading to serious neurological sequelae. We report the longitudinal evolution of the brain magnetic resonance imaging aspects of three cases of mother-to-child Chikungunya virus transmission. The first magnetic resonance imaging scan presented brain cavitations, with or without corpus callosum diffusion restriction. Follow-up scans showed reduction in the volume of cavitations, with resolution of the restricted diffusion. However, one patient presented with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Most studies (n = 35; 83,3%) were case reports and case series [9,[16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48][49][51][52][53]. The clinical and perinatal manifestations of pregnancy and the outcome of gestation were described in ten studies [9,10,[16][17][18][19][20][21]23,25,27,[49][50][51]. Stillbirths and miscarriage associated with CHIKV vertical transmission with laboratory evidence were reported in three studies …”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (n = 35; 83,3%) were case reports and case series [9,[16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48][49][51][52][53]. The clinical and perinatal manifestations of pregnancy and the outcome of gestation were described in ten studies [9,10,[16][17][18][19][20][21]23,25,27,[49][50][51]. Stillbirths and miscarriage associated with CHIKV vertical transmission with laboratory evidence were reported in three studies …”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…All included studies (n = 42) reported CHIKV vertical transmission confirmed by laboratory and clinical-epidemiological evidence in pregnant women (Table 1). The maternal infection diagnosis was confirmed by molecular and serological tests in 31 (73.8%) studies [6,9,10,[16][17][18][19][20][21][22][23][24][25][26][27][28]30,31,[33][34][35]39,41,[43][44][45][47][48][49][50][51]53,54] and in 243 (96.8%) women.…”
Section: Pregnancy Outcome Clinical and Perinatal Characteristics Of The Pregnant Women (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, long-term sequelae can occur after infection. During the CHIKV epidemic in Brazil, atypical and severe cases were reported, including neuronal impairment in adults and newborns (mother-to-child infection) [ 149 , 150 , 151 , 152 , 153 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%